2021
DOI: 10.1016/j.isci.2021.102218
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of TxNIP by ChREBP and FoxO1 in liver

Abstract: Summary TxNIP (Thioredoxin-interacting protein) is considered as a potential drug target for type 2 diabetes. Although TxNIP expression is correlated with hyperglycemia and glucotoxicity in pancreatic β cells, its regulation in liver cells has been less investigated. In the current study, we aim at providing a better understanding of Txnip regulation in hepatocytes in response to physiological stimuli and in the context of hyperglycemia in db/db mice. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…TXNIP affects the homeostasis of myocardial cells under ischemic stress by regulating redox status [52] . The study found that CD44 and TGF-β1 Participate in the development of diabetes nephropathy and liver brosis [53][54][55][56] . The pathogenesis of heart diseases is related to the activation of cardiac broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP affects the homeostasis of myocardial cells under ischemic stress by regulating redox status [52] . The study found that CD44 and TGF-β1 Participate in the development of diabetes nephropathy and liver brosis [53][54][55][56] . The pathogenesis of heart diseases is related to the activation of cardiac broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This factor was upregulated in the mouse intestine during chronic consumption of high-fructose diet and elevated expression of GLUT5 [ 70 ]. There is a study suggesting that Txnip promotes the nuclear translocation of ChREBP factor, enhancing its binding to the promoter region of Slc2a5 gene due to the presence of two carbohydrate response elements (ChoRE) for binding of ChREBP [ 71 ], as well as influences methylation of the Slc2a5 gene [ 68 ]. ChREBP via ChoRE also regulates the expression of other genes encoding enzymes involved in fructose metabolism, such as ketohexokinase (KHK), which intensifies fructose metabolism-increasing hepatic lipogenesis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TXNIP itself is a key regulator of hepatic glucose production, and gene silencing of hepatic TXNIP caused fasting hypoglycaemia and evoked a decreased response to glucagon 68 . Additionally, suppression of TXNIP expression in the liver of diabetic db/db mice was sufficient to control hyperglycaemia, along with normalized expression of key genes that promote hepatic gluconeogenesis 69 . The effects of TXNIP on hepatic glucose production have been linked to the modulatory effects of TXNIP on the cellular redox system, which is known to control gluconeogenesis 70,71 .…”
Section: Discussionmentioning
confidence: 99%